ANALISIS PENGARUH RETURN ON EQUITY (ROE), DEBT TO EQUITY RATIO (DER), PRICE TO BOOK VALUE (PBV), DAN EARNING PER SHARE (EPS) TERHADAP RETURN SAHAM: (Studi Empiris pada Perusahaan LQ-45 yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019) - Linda Avishadewi; Sulastiningsih Sulastiningsih (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
This study aims to analyze the influence of Return On Equity (ROE), Debt to Equity Ratio (DER), Price to Book Value (PBV), and Earning Per Share (EPS) partially and simultaneously to stock returns. The type of data used is secondary data sourced from the official website of the Indonesia Stock Exchange (IDX) and the companys official website. The population that used in this study were LQ-45 companies listed on the Indonesia Stock Exchange for the period 2015-2019. The samples are picked from 25 companies chosen by purposive sampling method. Data collection use documentation techniques on the companys annual financial statements and company stock prices. The data analysis technique used is a multiple linear regression analysis. The result of this study shows that ROE has a negative and significant effect on stock returns, DER has a positive and significant effect on stock returns, PBV has a positive and significant effect on stock returns, and EPS has a positive and significant effect on stock returns. The simultaneously result show that ROE, DER, PBV, and EPS have a significant effect on stock returns.